The Impact of Energy Transition on the Geopolitical Importance of Oil-Exporting Countries - Mohsen Salimi; Majid Amidpour (World, 2022)
With the changes that have taken place in energy-related technologies, the United States has been less affected by the geopolitical risks associated with the supply of fossil fuel energy resources, especially crude oil. When the price of oil is low, the geopolitical situation of U.S. energy contrasts with that of other oil-producing countries, which are facing financial pressure due to low oil prices and a high domestic energy demand. Many other countries have been supplying crude oil compared to half a century ago, reducing the strategic importance of major oil exporters, such as key OPEC members in the Persian Gulf. The shale oil revolution in the United States and the transition of energy in countries around the world to more sustainable energy sources, especially renewable energy, have reduced the importance of security in the Arab states of the Persian Gulf for U.S. politicians, which will be intensified in the future. Especially from the middle of the Carter administration period, U.S. politicians saw the security of the Arab states of the Persian Gulf as a prerequisite for securing energy supplies for the U.S. economy, but that has changed. Despite the disruption of Russia’s fossil fuel energy supply, as one of the main energy suppliers, due to sanctions from February 2022, the global energy carriers’ prices are relatively under control. Energy transition is one of the main contributors to lowering the impact of fossil fuel energy supply disruptions on the global economy.